Reasons For Dental Visits of Children at Dental Outpatient Department of a Tertiary Hospital in Dhaka: A Cross- Sectional Study (Journal of Dentistry and Allied Science, 2025)
Background: Children aged from 1-14 are susceptible to wide range of dental and oral problems including trauma that need dental support. The dental outpatient department serves a vital point for management of dental problems. The objective of the study is to assess the reasons and pattern of dental visits and associated factors among Bangladeshi children attending the dental outpatient department of a tertiary hospital in Dhaka. Methodology: This was a cross-sectional observational study. The study sample comprised 450 children, aged between 1-14 years including both male and female. The respondents were asked about the frequency and reasons for their dental visits, oral hygiene practices, the experience of oral problems during the past 12 months, monthly income and educational attainment of parents. The descriptive and inferential statistics were calculated using Microsoft Excel 2010. Result: The mean age of the surveyed children was 8.3 (±0.7) years; 52% were girls and 48% were boys. The majority of the parents were with higher secondary school education or above and only 6% were illiterate. The majority (57.78%) of the children brushed their teeth once a day and 34.88% do not brush every day. 66.33% children used toothpaste. 36.44% children visited the dentist for the first time, 38.22% children visited the dentist once in the past 12 months, 8.44% visited the dentist twice and but 16.89% children visited the dentist more than twice. 39.6% children visit the dentist during for problems with teeth, 19.1% visit the dentist for problem related to gingiva and 10.7% visited for dental emergency. Conclusion: Dental emergencies were common reason of dental visit in tertiary hospitals. The patterns of dental visit of children appear to be problem-initiated rather than for primary prevention or checkups.Journal of Dentistry and Allied Science, Vol. 8 No 2: 13-19